Reputation: 738
There is mysql table foo
:
a | b | c
----------
1 | 2 | 0
2 | 3 | 1
3 | 4 | 0
and a query
SELECT a-b as subA, b-a as subB FROM foo;
subA | subB
-----------
-1 | 1
-1 | 1
-1 | 1
How can I select a-b as sum
if c = 0 and b-a as sum
if c = 1, so that I have this result:
sum
---
-1
1
-1
Upvotes: 1
Views: 184
Reputation: 10163
This is pretty simple (look in SQLize.online):
SELECT
a-b as subA,
b-a as subB,
CASE
WHEN c = 0 THEN a-b
WHEN c = 1 THEN b-a
END as sum
FROM foo;
Result:
+======+======+=====+
| subA | subB | sum |
+======+======+=====+
| -1 | 1 | -1 |
+------+------+-----+
| -1 | 1 | 1 |
+------+------+-----+
| -1 | 1 | -1 |
+------+------+-----+
Upvotes: 1
Reputation: 222482
You can use a case
expression:
select f.*,
case c
when 0 then a - b
when 1 then b - a
end as res
from foo f
If c
is always 0
or 1
, we can get a little fancy with sign()
:
select f.*, sign(c - 0.5) * (b - a) as res
from foo f
Upvotes: 1